2018
DOI: 10.3389/fpsyg.2017.01996
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Inquiry into the Burnout Experience of Australian Solo-Practicing Clinical Psychologists

Abstract: Objective: Burnout is conceptualized as a syndrome that consists of emotional exhaustion, depersonalization, and decreased personal accomplishment. Despite the increased frequency and severity of burnout in the Western world, there is limited published research regarding the experiences of clinical psychologists who have had burnout. The present study examines clinical psychologists’ different experiences of burnout in Australia.Design and Methods: In the year 2015, six privately practicing and solo-employed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 31 publications
3
40
0
Order By: Relevance
“…The importance of social support in managing stress and burnout is well documented (Hobfoll, 1989 ; Halbesleben, 2006 ). Social support, work-based support and supervisor support have all been credited as a resource for reducing burnout in clinical psychologists (Hammond et al, 2017 ). Franco ( 2015 ) suggests that supervisors educate themselves and form open discussions with their clinicians, promoting self-awareness and self-care practices amongst those they supervise.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of social support in managing stress and burnout is well documented (Hobfoll, 1989 ; Halbesleben, 2006 ). Social support, work-based support and supervisor support have all been credited as a resource for reducing burnout in clinical psychologists (Hammond et al, 2017 ). Franco ( 2015 ) suggests that supervisors educate themselves and form open discussions with their clinicians, promoting self-awareness and self-care practices amongst those they supervise.…”
Section: Discussionmentioning
confidence: 99%
“…We found that none of the three workload variables were associated with either burnout facet. This was surprising, as previous systematic reviews (Hannigan et al, 2004; McCormack et al, 2018) and recent studies have suggested that workload, contracted hours, and caseload are linked with burnout in psychological therapists (Hammond et al, 2018; Kim et al, 2018). However, these recent studies were conducted outside the United Kingdom, and the present findings could be due to the UK healthcare delivery context, studies of NHS‐based therapists are more consistent with our present findings.…”
Section: Discussionmentioning
confidence: 96%
“…Maslach et al (2001) suggests supervision is a key protective factor against burnout. A recent qualitative study in psychological therapists supports this, suggesting that the quality of the relationship in terms of trust and support was particularly important (Hammond, Crowther, & Drummond, 2018). However, few quantitative studies have investigated the links between supervision and burnout in psychological therapists.…”
Section: Introductionmentioning
confidence: 91%
“…A possible program theory, based on CMO configurations, could be that experiencing low job demands and high job control helps an employee to exert control over one's own work, including adjustments that can be made (32,33,35,(37)(38)(39)(40). Heavy workload, overtime and high job strain reduce the chance for SAW, among employees with stress or depression (28,30,31,38). Job modifications help, however in a different way for white-versus blue-collar workers, due to the type of duties and work context (23,30,(41)(42)(43).…”
Section: Middle-range Program Theory 3: Perceived Job Characteristicsmentioning
confidence: 99%
“…Heavy workload, overtime and high job strain reduce the chance for SAW, among employees with stress or depression (28,30,31,38). Job modifications help, however in a different way for white-versus blue-collar workers, due to the type of duties and work context (23,30,(41)(42)(43).…”
Section: Middle-range Program Theory 3: Perceived Job Characteristicsmentioning
confidence: 99%